Development of a Rapid Diagnostic Kit for Congestive Heart Failure Using Recombinant NT-proBNP Antigen - Young-Ki Lee; Dong-Ok Choi; Ga-Yeon Kim (Medicina, 2021)
Background and Objectives: In patients with congestive heart failure, brain natriuretic peptide (BNP) and N-terminal prohormone of brain natriuretic peptide (NT-proBNP) are released due to excessive heart muscle expansion; they can be used for the early detection, progress monitoring, and treatment of congestive heart failure. Recently, considerable efforts have been made to develop an NT-proBNP-based biomarker for detecting heart failure. This study attempts to develop a rapid and accurate congestive heart failure diagnostic kit using NT-proBNP. Materials and Methods: A new gene based on NT-proBNP was selected, recombined, and expressed in Escherichia coli strains, and then monoclonal antibodies were produced using the hybridoma technique. Additionally, antigen-antibody reactivity was confirmed using indirect enzyme-linked immunosorbent assay (ELISA). Furthermore, the first pair and full-strip pair tests were conducted to select candidate clones; these were applied to a rapid diagnosis kit based on gold conjugates and compared with other currently available antigens. Results: NT-proBNP-based antigens with high specificity and monoclonal antibodies were produced, and the optimal antigen-antibody reactivity was confirmed using indirect ELISA. The first pair and full-strip pair tests were performed to select the optimal candidate clones, and a rapid diagnosis kit with excellent reactivity was developed by applying these to a rapid diagnosis kit based on gold conjugates. Conclusions: The development of this rapid diagnosis kit with excellent performance in congestive heart failure is expected to improve disease management by providing an early assessment of the risk of heart failure.